Design and control of a cable-driven rehabilitation robot for upper and lower limbs - Oyman, Efe Levent; Korkut, Muhammed Yusuf; Ylmaz, Cuneyt; Bayraktaroglu, Zeki Y.; Arslan, M. Selcuk (CAMBRIDGE UNIV PRESS, 2022)
The design and control of a cable-driven rehabilitation robot, which can be configured easily for exercising different articulations such as elbows, shoulders, hips, knees and ankles without requiring any orthosis, are introduced. The passive, active-assisted and active-resisted exercises were designed and implemented using impedance control. The controller could switch between exercises according to the force feedback. The effectiveness of the proposed controller was demonstrated by experimental studies. The robot was tested first with a dummy extremity and then with a healthy subject mimicking various types of patients during the tests. Experimental results showed that satisfactory closed-loop performances were achieved.
Keywords: Rehabilitation robot; Impedance control; Therapeutic exercise; Cable-driven robot; AIDED THERAPY; ARM; EXOSKELETON; DEVICE; WRIST; Robotics